Oral and anal carriage of Neisseria meningitidis among sexually active HIV-infected men who have sex with men in Denmark 2014–15 - Tinggaard, Michaela; Slotved, Hans-Christian; Fuursted, Kurt; Rosenstierne, Maiken Worsøe; Kronborg, Gitte; Lebech, Anne-Mette; Thorsteinsson, Kristina; Katzenstein, Terese L.; Storgaard, Merete; Holden, Inge Kristine; Johansen, Isik Somuncu; Benfield, Thomas (International journal of infectious diseases, 2021)
•The carriage rate of Neisseria meningitidis was 32% among HIV infected MSM.•Meningococci were detected in both oral and anal samples.•Non-groupable meningococci were most prevalent, followed by genogroup B.•Results support that sexual transmission of meningococci can occur. Outbreaks of invasive meningococcal disease (IMD) among men who have sex with men (MSM) caused by a hypervirulent, non-encapsulated Neisseria meningitidis (Nm) clone belonging to genogroup C have been described. We aimed to determine the oral and anal carriage rates and genogroups of Nm among MSM living with HIV. Sexually active MSM living with HIV were included. A questionnaire, an oral wash sample and an anal swab were collected at baseline and 12 months follow-up. Identification of Nm and genogrouping was performed using real-time polymerase chain reaction analysis. Among 82 MSM, the Nm carriage rate was 31.7% (95% CI 21.9–42.9) at baseline. The oral carriage rate was 24.4% (95% CI 15.6–35.1) and the anal rate was 11.0% (95% CI 5.1–19.8). Non-groupable Nm were most prevalent followed by genogroup B and genogroup Y. Rates were similar at follow-up. Strains of Nm were detected in both oral washes and anal samples in our study. Our results suggest that Nm may be transmitted sexually among MSM. Non-groupable Nm were predominant in our population and no genogroup C Nm were detected.